"Computational experience" Showing the influence of the fuel to sheat thermal conductance, in reactor fuel temperature predictions - Baigorria, Carlos A.; Harriague, Santiago; Lassmann, Klaus (Comisión Nacional de Energía Atómica; Argentina, 1981)
Fil: Baigorria, Carlos A. Comisión Nacional de Energía Atómica; Argentina